Investigation of the genome, taxonomy, and distribution of pigeon gammacoronavirus: insights into its relationships with other avian gammacoronaviruses - Tan, Sumei; Wang, Xiu; Zhuang, Qingye; Gong, Huanyu; Chen, Ruixu; Chen, Jiming; Liu, Dahai; Liao, Ming (Frontiers in Microbiology, 2025)
IntroductionVarious coronaviruses (CoVs) are pathogenic to humans and animals. Most pathogenic CoVs belong to the Orthocoronavirinae subfamily, which comprises the genera of Alphacoronavirus, Betacoronavirus, Gammacoronavirus, and Deltacoronavirus. Pigeon gammacoronavirus (PgCoV) is prevalent in pigeons but remains poorly characterized.MethodsIn this study, the first complete genome sequence of PgCoV was obtained through high-throughput sequencing and systematically analyzed along with other CoV genomic sequences.ResultsPgCoVs exhibited significant differences from other avian gammacoronaviruses in genomic structure, phylogenetic relationships, and N-glycosylation sites in the S protein. These differences warrant classifying PgCoVs and some Australian chicken gammacoronaviruses as two new species and justify removing one existing chicken gammacoronavirus species (Gammacoronavirus pulli), according to the demarcation criteria set by the International Committee on Taxonomy of Viruses. Sequence analysis also revealed that both minor mutations (e.g., nucleotide substitutions) and major mutations (e.g., frameshift mutations and genomic recombination) play key roles in the evolution of gammacoronaviruses. An epidemiological survey revealed a high prevalence of PgCoVs and other avian gammacoronaviruses in their respective poultry flocks, as well as cross-species transmission of these viruses. Furthermore, evidence supporting the PgCoV replication in intestinal and kidney tissues of pigeons was identified, indicating potential pathogenicity in the digestive and urinary systems. A specific, sensitive, and reproducible fluorescent RT-PCR assay for PgCoV detection was developed.DiscussionThis study expands our understanding of the genome, taxonomy, and distribution of PgCoVs and other avian gammacoronaviruses, which is significant for risk assessment, detection, and control of these viruses.